Hydronephrosis and survival in cervical cancer patients: The role of urinary diversion - María Esther Garza-Montúfar; Gibrán Domingo Carballo-Rosario; Carlos Marcel García-Pérez (Gynecologic Oncology Reports)
Objective: We aimed to assess the impact of urinary diversion on survival in patients with advanced cervical cancer (CC) and hydronephrosis. Additionally, we examined the influence of other patient factors and urinary diversion type on survival. Methods: A retrospective study analyzed survival in cervical cancer (CC) patients with hydronephrosis treated at two Mexican hospitals from 2011 to 2023. Patient data, including demographics, clinical, and pathological characteristics, were collected. Urinary diversion details and complications were recorded. Survival analysis was performed using Kaplan-Meier method and Cox regression model to identify predictors of survival. Results: A total of 228 cervical cancer patients presenting with hydronephrosis were analyzed. Median follow-up was 9 months. The majority of patients were in stage IVA (44.3 %), with 66.7 % exhibiting bilateral renal involvement. Urinary diversion was performed in 192 patients (84.2 %). Median overall survival (OS) was 15.5 months. Multivariate analysis identified stage, disease course, oncologic treatment, laterality, performance status, and urinary diversion as independent prognostic factors for survival. In patients undergoing urinary diversion, bilateral renal involvement (HR 2.0) and deteriorated performance status (HR 3.6) were risk factors for mortality. Neither the laterality (unilateral or bilateral) nor the type of diversion significantly affected overall survival. Conclusions: Survival in CC patients with hydronephrosis is influenced by factors such as: bilateral involvement, performance status, clinical stage, course and treatment of the underlying malignancy and urinary diversion. Urinary diversion improves survival, regardless of the specific diversion type or whether the diversion is unilateral or bilateral.